Children and Young Persons (Employment) Act 1966: the adequacy of the act in protecting the rights of children and young persons under employment in Malaysia / Dhiya Damia Shukri, Amir Afandi Shamsul Kamal and Muhammad Mohd Nasir - Shukri, Dhiya Damia; Shamsul Kamal, Amir Afandi; Mohd Nasir, Muhammad (2012)
The issue of protection of child workers in Malaysia is one where there are few attention received by the public. The current legislation that governs child workers is the Children and Young Persons (Employment) Act 1966 (hereinafter known as the CYPE Act). This project paper deals with the adequacy of the CYPE Act in protecting the rights of child workers in Malaysia. The result of the research is that, there are three separate issues that are found to be related to the ineffectiveness of the Act in safeguarding the rights of child workers. Firstly, it was found that the exceptions in working hours for children working in family-run establishments or in the agricultural sector had given rise to a high number of exploitation of child workers. Children working in the specified fields of work were required to work long hours and due to the lacunae in the CYPE Act itself, their working hours could not be adequately monitored. Secondly, the recent amendments of the CYPE Act had failed to ensure satisfactory enforcement of the provisions in the Act. Although the law was in existence, the lack of enforcement of its provisions had made what was to be a sufficient Act, ineffective in protecting the rights of child workers. Lastly, based on the research, it was found that there were no minimum wages with regards to child workers in Malaysia. Although the law has provided inquiry into wages for child workers, the question of who is to be responsible in making the inquiry has hindered the effectiveness of the law. In order to determine the adequacy of the CYPE Act in Malaysia, a comparative study was made with a similar Act from Australia. Based on the study, several lacunae in the CYPE Act was found especially regarding children in public entertainment. A thorough examination of Malaysia's adaptation of the ratified Convention on the Rights of the Child was also made as a guideline to determine whether the CYPE Act is adhering to international standards of child labour.